2015
DOI: 10.1103/physrevb.91.104302
|View full text |Cite
|
Sign up to set email alerts
|

Real-time decay of a highly excited charge carrier in the one-dimensional Holstein model

Abstract: We study the real-time dynamics of a highly excited charge carrier coupled to quantum phonons via a Holstein-type electron-phonon coupling. This is a prototypical example for the nonequilibrium dynamics in an interacting many-body system where excess energy is transferred from electronic to phononic degrees of freedom. We use diagonalization in a limited functional space (LFS) to study the nonequilibrium dynamics on a finite one-dimensional chain. This method agrees with exact diagonalization and the time-evol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 129 publications
(220 reference statements)
2
81
0
Order By: Relevance
“…43,[50][51][52][53] The wave function is represented as the matrix-product state form as |Ψ = σ1,σ2,...…”
Section: Introductionmentioning
confidence: 99%
“…43,[50][51][52][53] The wave function is represented as the matrix-product state form as |Ψ = σ1,σ2,...…”
Section: Introductionmentioning
confidence: 99%
“…[31] showed that for weak nearest-neighbor interaction V the integral over the bosonic Weiss field scales as dωIm[D(ω)] ∝ V 2 . Hence our phenomenological analysis shows that the enhancement of the relaxation due to the nonlocal interaction V and the corresponding V 2 scaling is consistent with a relaxation aided by the coupling to a bath of bosonic degrees of freedom (plasmons) [36,[43][44][45][46].…”
Section: B Enhanced Doublon Relaxation Due To Dynamical Screeningmentioning
confidence: 99%
“…Note added in proof: We would like to mention the recent publication of work by Dorfner et al [49], providing a comprehensive analysis of the single-electron Holstein mode in one dimension. Although the main focus of this paper is not in the adiabatic regime, the results for the weak-coupling regime are in agreement with our discussion.…”
Section: Discussionmentioning
confidence: 99%